Cinnamic acid Supplementation Regulates the Production of Licochalcone A, Liquirtigenin and Licoisoflavone B in Glycyrrhiza glabra Callus Cultures. - U. Vijayalakshmi; Abhilasha Shourie (International Journal of Phytomedicine, 2016)
Glycyrrhiza glabra is an ancient herbal medicine rich in large number of secondary metabolites which attribute to its therapeutic properties. These metabolites are usually obtained from field grown plants and their yields vary greatly on the basis of environmental conditions. Plant tissue culture can thus be a preferred method for consistent production of such metabolites. This study dealt with the enhancement of flavonoids through precursor feeding in callus cultures of G. glabra and investigated the influence of cinnamic acid on phenylalanine ammonia lyase (PAL) activity and production of licochalcone A, liquirtigenin and licoisoflavone B. Unorganized callus cultures were established from young leaf explants on Murashige and Skoog’s (MS) medium supplemented with NAA (1mg/l), BAP (0.5 mg/l) and various concentrations of cinnamic acid. Flavonoids were obtained from calli through solvent extraction and were identified and quantified through Gas-Chromatography Mass spectrometry. Cinnamic acid supplementation at appropriate concentrations (50mg/100ml for licochalcone A and liquirtigenin, and 125mg/100ml for licoisoflavone B) significantly increased their production to 1.28, 1.2 and 9.76 folds respectively. However, prolonged treatment of cinnamic acid at concentration beyond 50mg/100ml led to decrease in the production of liquirtigenin and licochalcone A , but caused fair increase in licoisoflavone B. Also cinnamic acid concentrations higher than 50mg/100ml reduced the activity of PAL enzyme due to its feedback inhibition, but at the same time might have modulated other intermediate enzymes of the pathway like chalcone isomerase favoring the formation of licoisoflavone B. Therefore, this study provides clear evidences of enzymatic regulation of phenylpropanoid pathway by cinnamic acid in G. glabra callus cultures.